2023
DOI: 10.1002/ijc.34536
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐target angiogenesis inhibitor combined with PD‐1 inhibitors may benefit advanced non‐small cell lung cancer patients in late line after failure of EGFR‐TKI therapy

Abstract: Treatments for NSCLC patients with EGFR-TKI resistance are limited. Given that immunotherapy and antiangiogenic agents may have synergistic antitumor effects, we aimed to analyze the effect of multi-target angiogenesis inhibitor anlotinib and immune checkpoint inhibitors (ICIs) combination therapy in NSCLC patients who failed EGFR-TKI. The medical records of lung adenocarcinoma (LUAD) patients with EGFR-TKI resistance were reviewed. After EGFR-TKI resistance, patients who simultaneously received anlotinib and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…However, cabozantinib plus atezolizumab only demonstrated modest activity in 30 patients with previously‐treated advanced EGFR ‐mutated NSCLC (ORR = 7%, DCR = 63%, median PFS = 2.7 months, and median OS = 6.1 months) 35 . In contrast, anlotinib combined with ICIs exhibited a longer median PFS (4.3 months vs 3.6 months, p = 0.005), and OS (14.2 months vs 9.0 months p = 0.029) than chemotherapy for the late‐line treatment of patients with NSCLC and EGFR‐TKI resistance 36 . Additionally, the phase 3 Orient‐31 trial reported that sintilimab plus the bevacizumab biosimilar IBI305 and chemotherapy led to significant improvements in PFS over chemotherapy alone in patients with advanced EGFR ‐mutated NSCLC after TKI failure (6.9 vs 4.3 months; p < 0.001) 37 .…”
Section: Discussionmentioning
confidence: 98%
“…However, cabozantinib plus atezolizumab only demonstrated modest activity in 30 patients with previously‐treated advanced EGFR ‐mutated NSCLC (ORR = 7%, DCR = 63%, median PFS = 2.7 months, and median OS = 6.1 months) 35 . In contrast, anlotinib combined with ICIs exhibited a longer median PFS (4.3 months vs 3.6 months, p = 0.005), and OS (14.2 months vs 9.0 months p = 0.029) than chemotherapy for the late‐line treatment of patients with NSCLC and EGFR‐TKI resistance 36 . Additionally, the phase 3 Orient‐31 trial reported that sintilimab plus the bevacizumab biosimilar IBI305 and chemotherapy led to significant improvements in PFS over chemotherapy alone in patients with advanced EGFR ‐mutated NSCLC after TKI failure (6.9 vs 4.3 months; p < 0.001) 37 .…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have demonstrated that immunotherapy shows clinical activity in LUAD [ 49 , 50 ]. In this research, the risk scores are highly correlated with immune checkpoint expression, including HAVCR2 and CTLA4.…”
Section: Discussionmentioning
confidence: 99%
“…In the IMpower 150 trial, the combination of ICIs, bevacizumab, and chemotherapy showed an advantage as a first-line treatment for nonsquamous NSCLC ( 27 ). Some studies have found good results with the combination of anlotinib and ICIs in a variety of tumors, including lung cancer ( 16 , 19 , 28 , 29 ). Our study found superior efficacy of anlotinib and PD-1 blockade combination therapy as second- and subsequent-line treatment of patients with advanced driver-negative LUAD, a subset of patients that few studies have focused on.…”
Section: Discussionmentioning
confidence: 99%
“…Combination strategy of anti-angiogenesis inhibitor and ICIs could counteract the immunosuppression, exerting synergistic antitumor effects. The efficacy and safety of anlotinib and ICIs combination therapy has been validated in several solid tumors, including advanced NSCLC as first-line treatment ( 16 - 19 ). This retrospective study aimed to explore the efficacy and safety of anlotinib and ICIs as a second- and subsequent-line treatment for advanced lung adenocarcinoma (LUAD) in patients without oncogenic driver alterations.…”
Section: Introductionmentioning
confidence: 99%